A Multi-institutional International Analysis of Textbook Outcomes Among Patients Undergoing Curative-Intent Resection of Intrahepatic Cholangiocarcinoma - Merath, Katiuscha (JAMA Surg, 2019)
IMPORTANCE: Composite measures may be superior to individual measures for the analysis of hospital performance and quality of surgical care. OBJECTIVE: To determine the incidence of a so-called textbook outcome, a composite measure of the quality of surgical care, among patients undergoing curative-intent resection of intrahepatic cholangiocarcinoma. DESIGN, SETTING, AND PARTICIPANTS: This cohort study involved an analysis of a multinational, multi-institutional cohort of patient from 15 major hepatobiliary centers in North America, Europe, Australia, and Asia who underwent curative-intent resection of intrahepatic cholangiocarcinoma between 1993 and 2015. Data analysis was conducted from April 2018 to May 2018. MAIN OUTCOMES AND MEASURES: Hospital variation in the composite end point of textbook outcome, defined as negative margins, no perioperative transfusion, no postoperative surgical complications, no prolonged length of stay, no 30-day readmissions, and no 30-day mortality. Secondary end points were factors associated with achieving textbook outcomes. RESULTS: Among 687 patients (of whom 370 [53.9%] were men; median patient age, 61 [range, 18-86] years) undergoing curative-intent resection of intrahepatic cholangiocarcinoma, a textbook outcome was achieved in 175 patients (25.5%). Being 60 years or younger (odds ratio [OR], 1.61 [95% CI, 1.04-2.49]; P = .03), absence of preoperative jaundice (OR, 4.40 [95% CI, 1.28-15.15]; P = .02), no neoadjuvant chemotherapy (OR, 2.57 [95% CI, 1.05-6.29]; P = .04), T1a/T1b-stage disease (OR, 1.58 [95% CI, 1.01-2.49]; P = .049), N0 status (OR, 3.89 [95% CI, 1.77-8.54]; P = .001), and no bile duct resection (OR, 2.46 [95% CI, 1.25-4.84]; P = .009) were independently associated with achieving a textbook outcome after resection. A prolonged length of stay had the greatest negative association with a textbook outcome. A nomogram to assess the probability of textbook outcome was developed and had good accuracy in both the training data set (area under the curve, 0.755) and validation data set (area under the curve, 0.763). CONCLUSIONS AND RELEVANCE: In this study, while hepatic resection for intrahepatic cholangiocarcinoma was performed with less than 5% mortality in specialized centers, a textbook outcome was achieved in only approximately 26% of patients. A textbook outcome may be useful for the reporting of patient-level hospital performance and hospital variation, leading to quality improvement efforts after resection of intrahepatic cholangiocarcinoma.